Do flood mitigation and natural habitat protection employment reduce youth offending? - Long, Michael A. (European journal on criminal policy and research, 2019)
The present study examines the association between employment and offending for a sample of young offenders who are paid to work in a pilot programme known as the Skill Mill. First, we analyse a sample of 39 youths over a period of 10 years (40 quarters) to determine whether Skill Mill employed youth are more likely to desist from offending than a control group of youth who are not employed in the Skill Mill. Those youths employed by the Skill Mill committed 1.12 fewer offences per quarter than the control group (p < 0.001). In addition, offending rates among the Skill Mill youths decreased by 0.99 offences per quarter after they began work (p < 0.001). Next, we review results from semi-structured interviews with current Skill Mill employees and their supervisor that helps to unpack why the Skill Mill has been successful in promoting desistance. We conclude that programmes like the Skill Mill can mark an important turning point, and more specifically, a hook for change in the lives of young offenders.